Patterns And Trends In Tarannum Qurʾān Studies From 2011-2018: A Thematic Review In The Field Of Tarannum Al-qurʾān - Nurul Auji Hasbullah; Ahmad Sanusi Azmi; Adnan Mohamed Yusoff (International Islamic University Malaysia, 2024)
Volume: 6 No: 2